Information adoption behavior in online healthcare communities from the perspective of personality traits - Zhu, Yiping; Jiang, Hong; Zhou, Zan (Frontiers in Psychology, 2022)
Improving standards of living have resulted in an increased focus on health and image management. In a context where the quality of healthcare information is unguaranteed, the adoption behavior intention of online health information varies greatly. Hence, it is essential to take effective measures to guide community users to obtain high-quality information on demand. From the perspective of personality traits, the present paper studied the influencing factors and mechanisms of adoption behavior intention of healthcare information in online healthcare communities as well as the moderating effects of social support. A quantitative analysis of 380 respondents revealed positive associations between five personality dimensions and the adoption behavior intention of healthcare information - extraversion, agreeableness,conscientiousness,neuroticism,,and openness. The study also determined that health concerns and health-related self-efficacy played a mediating role across various degrees between the conscientiousness and adoption behavior intention of healthcare information. As an important contextual factor influencing health outcomes, social support is common in online healthcare communities. The paper examined the effect of the interaction between inner traits and social support on adoption behavior intention. Perceived self-esteem support strengthened the indirect effect of conscientiousness on adoption behavior intention mediated by health concern and health-related self-efficacy. Additionally, the impact of high neuroticism interacted with low level of perceived self-esteem support on adoption behavior intention was significant. Likewise, emotional supportive information did not help in facilitating the adoption behavior intention in terms of all five personality traits, and negatively influence the adoption behavior intention for individuals high in neuroticism and agreeableness. The possible explanation for results were discussed with the intention of understanding the psychological mechanisms which guides adoption behavior intention.